1999
DOI: 10.1093/carcin/20.10.1945
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inducible cyclooxygenase and inducible nitric oxide synthase by apigenin and related flavonoids in mouse macrophages

Abstract: Prostaglandins biosynthesis and nitric oxide production have been implicated in the process of carcinogenesis and inflammation. In this study, we investigated the effect of various flavonoids and (-)-epigallocatechin-3-gallate on the activities of inducible cyclooxygenase (COX-2) and inducible nitric oxide synthase (iNOS) in lipopolysaccharide (LPS)-activated RAW 264.7 macrophages. Apigenin, genistein and kaempferol were markedly active inhibitors of transcriptional activation of COX-2, with IC(50) < 15 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
330
4
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(363 citation statements)
references
References 42 publications
16
330
4
7
Order By: Relevance
“…Flavonoids also have anti-inflammatory effects through its inhibition of the cyclooxygenase pathway [33] . That the extract inhibited neurogenic and non-neurogenic pains as well as narcotic pains may in part explain the mechanisms of its action and these effects are due to the presence of phytochemical components in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids also have anti-inflammatory effects through its inhibition of the cyclooxygenase pathway [33] . That the extract inhibited neurogenic and non-neurogenic pains as well as narcotic pains may in part explain the mechanisms of its action and these effects are due to the presence of phytochemical components in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties of apigenin are evident in studies that have shown suppression of LPS-induced cyclooxygenase-2 and nitric oxide synthase-2 activity and expression in mouse macrophages (40). In a separate study, apigenin treatment resulted in suppression of the constitutive and tumor necrosis factor (TNF) ·-induced nuclear factor (NF)-κB activation in human umbilical vein endothelial cells (41).…”
Section: Achillea Millefoliummentioning
confidence: 99%
“…Genistein effectively suppresses the COX-2 promoter activity with and without tumor growth factor-α-stimulation in DLD-1 colon cancer cells [73]. Genistein strongly represses the transcriptional activation of COX-2 in macrophages [67], and consistently inhibits COX-2 expression by blocking the LPS-mediated tyrosine kinase signal transduction pathway [92]. Using a β-galactosidase reporter gene system in human colon cancer cells, Mutoh et al [73] showed that genistein suppresses the COX-2 promoter activity in the presence or absence of tumor necrosis factor-α stimulation.…”
Section: Genisteinmentioning
confidence: 99%